Nrf2-mediated mechanistic pathways of celastrol nephroprotection: disrupting the oxidative-inflammatory-apoptotic axis in cypermethrin toxicity - Albrakati, Ashraf (Frontiers in Pharmacology, 2025)
BackgroundCypermethrin, a widely used synthetic pyrethroid insecticide, accumulates in renal tissue causing kidney damage through incompletely understood mechanisms. This study evaluated celastrol’s nephroprotective effect against cypermethrin-induced kidney injury in rats.MethodsFive groups of male Wistar rats (n = 8 each) received daily treatments for 28 days: control, cypermethrin (25 mg/kg), celastrol (2 mg/kg), and celastrol + cypermethrin at low (1 mg/kg) or high (2 mg/kg) doses. Renal parameters, oxidative stress markers, inflammatory mediators, and apoptotic indicators were assessed using spectrophotometric assays, ELISA, qRT-PCR, and histology.ResultsCypermethrin impaired renal function, increased kidney weight, and elevated Kidney Injury Molecule-1 (KIM-1) levels. It significantly suppressed antioxidant defenses by reducing both the activities and mRNA expression of CAT, SOD, GPx, and GR, alongside GSH depletion and elevated oxidative markers (MDA, NO). Cypermethrin also downregulated the protein and gene expression of Nfe2l2, along with its downstream targets Hmox1, GCLC, and NQO1. Inflammatory responses were enhanced, as shown by upregulated TNF-α, IL-1β, NF-κB proteins and increased NOS2 expression. Apoptosis was induced through elevated Bax, cytochrome c, and caspase-3 protein and gene expression, while both Bcl-2 protein and Bcl2 mRNA were significantly reduced. Correlation analysis revealed significant inter-pathway connections, suggesting that oxidative stress as upstream trigger for inflammation and apoptosis. Celastrol treatment dose-dependently reversed these alterations, with the high dose restoring antioxidant and anti-apoptotic profiles more effectively than the low dose. Histopathological findings corroborated these results.ConclusionCelastrol protects against cypermethrin nephrotoxicity through modulation of antioxidative, anti-inflammatory, and anti-apoptotic mechanisms. Correlation analysis suggests a potential role for Nrf2 in celastrol’s integrated nephroprotective effects.